A preparation process for high-stiffness toothpaste packaging tube

By using homemade high-stress coextrusion film as the inner layer material in the toothpaste packaging pipe, using multiple hydrogen bond systemized silane coupling agent to modify the interface stable carbon fiber and nylon resin PA to make PA-CNF composite material, and mix it with high-density polyethylene resin to make PE-CNF-PA masterbatch, the problem of toothpaste hose is too low, and the stiffness performance is significantly improved and cost optimization is achieved.

CN119217698BActive Publication Date: 2025-03-07SUZHOU ZIJIN PLASTIC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411730215.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The stiffness of the toothpaste hose at the tail is too low, which leads to wrinkles at the tail after filling, resulting in leakage and unstable filling quality. Simply increasing the thickness of the sheet to increase the stiffness may increase procurement costs.

Method used

The high-stress toothpaste packaging pipe made of the outer layer PE film, the adhesive layer EAA film, the intermediate layer aluminum foil, the adhesive layer EAA film and the inner layer homemade high-stress coextrusion film were used to prepare the high-stress toothpaste packaging pipe made by the high-speed solvent-free composite process by the modified interface stable carbon fiber and nylon resin PA by multiple hydrogen bond systemized silane coupling agent to make the PA-CNF composite material, and mixed with high-density polyethylene resin to prepare the PE-CNF-PA masterbatch.

Benefits of technology

The stiffness performance of the inner layer material of the toothpaste packaging pipe has been significantly improved, with a stiffness value of more than 5mN·m and a tensile strength of more than 35MPa, which not only optimizes procurement costs but also reduces production losses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119217698B_ABST
    Figure CN119217698B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of toothpaste packaging tubes, in particular to a preparation process of a high-stiffness toothpaste packaging tube. The high-stiffness toothpaste packaging tube is prepared by a high-speed solvent-free composite process of an outer PE film, a first adhesive layer, an intermediate aluminum foil, a second adhesive layer and an inner high-stiffness co-extruded film. The preparation method of the high-stiffness co-extruded film comprises: compounding an interface-stabilized carbon fiber carrying a multiple hydrogen bond system with a nylon resin PA to obtain a PA-CNF composite material, and mixing and granulating the composite material with a high-density polyethylene resin under the action of a compatibilizer maleic anhydride grafted polyethylene resin to obtain a PE-CNF-PA masterbatch; using the PE-CNF-PA masterbatch as a modifying agent for an eleven-layer co-extruded film, adopting an eleven-layer co-extrusion blow molding process, and preparing a high-stiffness co-extruded film, wherein the stiffness value of the product reaches more than 5mN·m, and the product can be used as an inner layer material of the high-stiffness toothpaste packaging tube.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of toothpaste packaging tubes, in particular to a preparation process of a high-stiffness toothpaste packaging tube. Background Art

[0002] At present, the composite hose for toothpaste is generally aluminum-plastic composite hose. Aluminum-plastic composite hose is a kind of hose packaging container made by compounding aluminum foil and plastic film into sheets and processing them through a tube making machine. Because it has good barrier and oxidation resistance, flexible printing methods, excellent printing effects, high bursting strength, comfortable feel, good anti-counterfeiting effect and other characteristics, it has been widely used in the packaging of various paste products.

[0003] Toothpaste products are generally produced by tail filling, which has certain requirements for the stiffness of the tail of the composite hose for toothpaste. If the stiffness of the hose tail is too low, the tail of the tube is prone to wrinkles and uneven surfaces when the tail is heat-sealed and compressed after filling, causing abnormalities such as leakage, leading to unstable filling quality and loss.

[0004] The study found that if the thickness of the toothpaste tube sheet is low and the diameter is large, the stiffness of the tube tail will be small, and the production loss caused by the tail seal wrinkles will be high. However, simply increasing the thickness of the sheet to improve the stiffness of the tube tail may also increase the procurement cost. Therefore, it is necessary to conduct research and development and design on the stiffness of the inner layer material used at the tail of the hose to achieve the purpose of optimizing procurement costs and reducing production losses at the same time.

[0005] Stiffness refers to the unit resistance torque generated when the material is bent within the range of elastic deformation. There are currently two main methods to enhance the stiffness of plastics: the first is to select plastics with high stiffness for compounding (nylon, polyetheretherketone, polyimide, polyphenylene sulfide, etc.), and the second is to add inorganic reinforcing fillers (carbon fiber, calcium carbonate, talcum powder, etc.). Summary of the invention

[0006] The invention provides a high-stiffness toothpaste packaging tube, which is prepared by a high-speed solvent-free composite process of an outer layer (PE film), an adhesive layer (EAA film), an intermediate layer of aluminum foil Al, an adhesive layer (EAA film) and an inner layer (self-made high-stiffness co-extruded film) which are arranged in sequence. The self-made high-stiffness co-extruded layer has the technical effect of significantly improving the stiffness performance of the inner layer material of the toothpaste packaging tube.

[0007] A preparation process of a high-stiffness toothpaste packaging tube, wherein the high-stiffness toothpaste packaging tube is prepared by a high-speed solvent-free composite process of an outer PE film, a first adhesive layer, an intermediate aluminum foil, a second adhesive layer and an inner high-stiffness co-extruded film;

[0008] Among them, the formula and dosage of each layer of high stiffness co-extrusion film are as follows:

[0009] First layer: The formula is 50-70 parts by weight of low-density polyethylene resin LDPE, 30-40 parts by weight of linear low-density polyethylene resin LLDPE and 3-10 parts by weight of composite additives, with an amount of 5-15 parts by weight;

[0010] The second layer: the formula is 60-80 parts by weight of high-density polyethylene resin HDPE and 20-40 parts by weight of metallocene polyethylene resin m-LLDPE, the amount is 5-15 parts by weight;

[0011] The third layer: the formula is 50-70 parts by weight of low-density polyethylene resin LDPE and 30-50 parts by weight of metallocene polyethylene resin m-LLDPE, the amount is 3-10 parts by weight;

[0012] The fourth layer: the formula is 100 parts by weight of maleic anhydride grafted polyethylene resin PE-g-MAH, the amount is 1-5 parts by weight;

[0013] The fifth layer: the formula is 95-99 parts by weight of low-density polyethylene resin LDPE and 1-5 parts by weight of ethylene-vinyl alcohol copolymer resin EVOH, the amount is 5-15 parts by weight;

[0014] The sixth layer: The formula is 30-50 parts by weight of high-density polyethylene resin HDPE and 50-70 parts by weight of PE-CNF-PA masterbatch, with an amount of 20-30 parts by weight;

[0015] The formula of PE-CNF-PA masterbatch is: 20-40wt% high-density polyethylene resin HDPE, 50-70wt% PA-CNF composite material and 5-15wt% maleic anhydride grafted polyethylene resin PE-g-MAH;

[0016] The preparation method of the PA-CNF composite material is as follows: the interface-stabilized carbon fiber and the nylon resin PA are composited by self-assembling the interface-stabilized carbon fiber with the multiple hydrogen bonding systems on the surface of the interface-stabilized carbon fiber with the amide groups on the main chain of the nylon resin PA molecule;

[0017] The mass ratio of the interface-stabilized carbon fiber loaded with multiple hydrogen bonding systems to the nylon resin PA in the PA-CNF composite material is 1:(5-10);

[0018] The seventh layer: the formula is 95-99 parts by weight of low-density polyethylene resin LDPE and 1-5 parts by weight of ethylene-vinyl alcohol copolymer resin EVOH, the amount is 5-15 parts by weight;

[0019] The eighth layer: the formula is 100 parts by weight of maleic anhydride grafted polyethylene resin PE-g-MAH, the amount is 1-5 parts by weight;

[0020] Ninth layer: The formula is 50-70 parts by weight of low-density polyethylene resin LDPE and 30-50 parts by weight of metallocene polyethylene resin m-LLDPE, with an amount of 3-10 parts by weight;

[0021] The tenth layer: the formula is 60-80 parts by weight of high-density polyethylene resin HDPE and 20-40 parts by weight of metallocene polyethylene resin m-LLDPE, the amount is 5-15 parts by weight;

[0022] The eleventh layer: The formula is 50-70 parts by weight of low-density polyethylene resin LDPE and 30-50 parts by weight of linear low-density polyethylene resin LLDPE, with the usage amount being 5-15 parts by weight.

[0023] Preferably, the method for preparing the interface-stabilized carbon fiber carrying a multiple hydrogen bond system is as follows: the silanol functional groups obtained by the hydrolysis reaction of the multiple hydrogen bond system silane coupling agent are subjected to a dehydration condensation reaction with the hydroxyl functional groups on the surface of the hydroxylated carbon fiber, and the multiple hydrogen bond system silane coupling agent is modified on the surface of the carbon fiber to prepare the interface-stabilized carbon fiber carrying a multiple hydrogen bond system.

[0024] Preferably, the multiple hydrogen bond system silane coupling agent is multiple hydrogen bond system silane coupling agent I or multiple hydrogen bond system silane coupling agent II.

[0025] Preferably, the preparation method of the multiple hydrogen bond system silane coupling agent I is:

[0026] The -NH2 functional group of 2-amino-4-hydroxy-6-methylpyrimidine reacts with the isocyanate group of p-phenylene diisocyanate by addition reaction, and the molar ratio of 2-amino-4-hydroxy-6-methylpyrimidine to p-phenylene diisocyanate is controlled to be 1:(2-10) to generate a multi-hydrogen bond system monomer;

[0027] The multiple hydrogen bond system silane coupling agent I is prepared by allowing the isocyanate group of the multiple hydrogen bond system monomer to undergo an addition reaction with the -NH2 functional group of 3-aminopropyltrimethoxysilane, and controlling the molar ratio of the multiple hydrogen bond system monomer to 3-aminopropyltrimethoxysilane to be 1:(1.01-1.08).

[0028] Preferably, the preparation method of the multiple hydrogen bond system silane coupling agent II is:

[0029] Firstly, the isocyanate group of the multiple hydrogen bond system monomer reacts with the -NH2 functional group of N,N-bis(3-aminopropyl)methylamine to generate a multiple hydrogen bond system tertiary amine monomer;

[0030] Then, the tertiary amine functional group of the multiple hydrogen bond system tertiary amine monomer and the chlorine functional group of 3-chloropropyltrimethoxysilane are quaternized by the nucleophilic substitution mechanism to prepare the multiple hydrogen bond system silane coupling agent II.

[0031] The molar ratio of the multiple hydrogen bond system monomer, N,N-bis(3-aminopropyl)methylamine and 3-chloropropyltrimethoxysilane is controlled to be (2.01-2.08):1:(1.01-1.08).

[0032] Preferably, the mass ratio of the silane coupling agent with multiple hydrogen bond system to the hydroxylated carbon fiber in the interface-stabilized carbon fiber carrying multiple hydrogen bond system is 1:(1-5).

[0033] Preferably, the hydroxylated carbon fiber has a diameter of 150-200 nm and a length of 10-20 μm.

[0034] Preferably, the composite auxiliary agent includes 0.5-5 parts by weight of antioxidant 168, 0.1-3 parts by weight of antioxidant 1010 and 0.5-5 parts by weight of anti-ultraviolet agent UV-329.

[0035] Beneficial effects: The present invention first designs and synthesizes a multiple hydrogen bond system silane coupling agent, and modifies the multiple hydrogen bond system silane coupling agent on the surface of carbon fiber to prepare an interface-stabilized carbon fiber carrying a multiple hydrogen bond system; then, the multiple hydrogen bond system carried on the surface of the interface-stabilized carbon fiber and the amide group on the main chain of the nylon resin PA molecule undergo self-assembly, and the interface-stabilized carbon fiber and the nylon resin PA are compounded to obtain a PA-CNF composite material; finally, the PA-CNF composite material is used as a stiffness modification raw material, and is mixed and granulated with a high-density polyethylene resin under the action of a compatibilizer maleic anhydride grafted polyethylene resin to prepare a PE-CNF-PA masterbatch;

[0036] A high-stiffness co-extruded film is prepared by using PE-CNF-PA masterbatch as a modifying agent for an eleven-layer co-extruded film and adopting an eleven-layer co-extrusion blow molding process. The stiffness value of the product reaches more than 5mN·m, and the tensile strength is as high as more than 35MPa. That is, the present invention provides an eleven-layer co-extruded film with very excellent stiffness performance, which can be used as the inner layer material of a high-stiffness toothpaste packaging tube. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is the chemical structural formula of the multi-hydrogen bond systematized monomer;

[0038] Figure 2 is the chemical structural formula of the multi-hydrogen bond system silane coupling agent I;

[0039] Figure 3It is the chemical structure formula of the multi-hydrogen bond system silane coupling agent II;

[0040] Figure 4 These are the performance test results of the self-made high-stiffness co-extruded film used in high-stiffness toothpaste packaging tubes. DETAILED DESCRIPTION

[0041] The main raw materials used in the present invention are shown in Table 1.

[0042] Table 1 Experimental raw materials

[0043]

[0044] Experimental Example 1:

[0045] Preparation of a multi-hydrogen bond system monomer: The -NH2 functional group of 2-amino-4-hydroxy-6-methylpyrimidine reacts with the isocyanate group of p-phenylene diisocyanate by addition reaction, and the molar ratio of 2-amino-4-hydroxy-6-methylpyrimidine to p-phenylene diisocyanate is controlled to be 1:5 to generate a multi-hydrogen bond system monomer, whose chemical structure is as follows: Figure 1 As shown;

[0046] The specific experimental steps for preparing the multiple hydrogen bond system monomer are as follows: under the protection of nitrogen, 1.3 g of 2-amino-4-hydroxy-6-methylpyrimidine, 8.0 g of p-phenylene diisocyanate and 80 mL of dimethyl sulfoxide are added to a three-necked flask, the temperature is raised to 100 ° C and stirred for reaction for 12 hours, cooled to room temperature, and the excess p-phenylene diisocyanate is repeatedly washed with acetonitrile to remove the excess p-phenylene diisocyanate, and vacuum dried to obtain the multiple hydrogen bond system monomer;

[0047] The nuclear magnetic resonance hydrogen spectrum of the multi-hydrogen bond system monomer is characterized as follows: 1 H NMR (DMSO-d6, 400MHz) δ: 2.53 (s, 3H), 5.92 (s, 1H), 7.48-7.54 (m, 4H), 8.06 (s, 1H), 9.23 (s, 1H), 10.60 (s, 1H). Embodiment 2:

[0048] Preparation of multi-hydrogen bond system silane coupling agent I: The isocyanate group of the multi-hydrogen bond system monomer reacts with the -NH2 functional group of 3-aminopropyltrimethoxysilane by addition reaction, and the molar ratio of the multi-hydrogen bond system monomer to 3-aminopropyltrimethoxysilane is controlled to be 1:1.04 to generate a multi-hydrogen bond system silane coupling agent I, whose chemical structure is as follows: Figure 2 As shown;

[0049] The specific experimental steps for preparing the multi-hydrogen bond system silane coupling agent I are as follows: under the protection of nitrogen, 2.8 g of the multi-hydrogen bond system monomer, 1.8 g of 3-aminopropyltrimethoxysilane and 50 mL of dimethyl sulfoxide are added to a three-necked flask, the temperature is raised to 100 ° C and stirred for reaction for 10 hours, cooled to room temperature, the solvent is removed by rotary evaporation, and vacuum dried to obtain the multi-hydrogen bond system silane coupling agent I;

[0050] The nuclear magnetic resonance hydrogen spectrum of the multi-hydrogen bond system silane coupling agent I is characterized as follows: 1 H NMR (DMSO-d6, 400MHz) δ: 0.66-0.69 (t, 2H), 1.64-1.72 (m, 2H), 2.52 (s, 3H), 3.15-3.20 (m, 2H), 3.57 (s, 9H) ), 5.85 (s, 1H), 6.53-6.56 (t, 1H), 7.56-7.60 (m, 4H), 8.57 (s, 1H), 8.88 (s, 1H), 9.64 (s, 1H), 10.91 (s, 1H).

[0051] Experimental Example 3:

[0052] Preparation of multiple hydrogen bond system silane coupling agent II:

[0053] Firstly, the isocyanate group of the multiple hydrogen bond system monomer reacts with the -NH2 functional group of N,N-bis(3-aminopropyl)methylamine to generate a multiple hydrogen bond system tertiary amine monomer;

[0054] Then, the tertiary amine functional group of the multiple hydrogen bond system tertiary amine monomer reacts with the chlorine functional group of 3-chloropropyltrimethoxysilane to form a multiple hydrogen bond system silane coupling agent II by using a nucleophilic substitution mechanism;

[0055] The molar ratio of the multiple hydrogen bond system monomer, N,N-bis(3-aminopropyl)methylamine and 3-chloropropyltrimethoxysilane is controlled to be 2.03:1:1.02. The chemical structure of the multiple hydrogen bond system silane coupling agent II is as follows: Figure 3 As shown;

[0056] The specific experimental steps for preparing the multiple hydrogen bond system silane coupling agent II are as follows: under the protection of nitrogen, 2.9g of multiple hydrogen bond system monomer, 0.7g of N,N-bis(3-aminopropyl)methylamine and 50mL of dimethyl sulfoxide are added to a three-necked flask, the temperature is raised to 100°C and stirred for reaction for 15h, and then cooled to room temperature to obtain a multiple hydrogen bond system tertiary amine monomer, and then 0.9mL of 3-chloropropyltrimethoxysilane is slowly added to the three-necked flask, the temperature is raised to 60°C and stirred for reaction for 5h, cooled to room temperature, the solvent is removed by rotary evaporation, and vacuum drying is performed to obtain a multiple hydrogen bond system silane coupling agent II;

[0057] The nuclear magnetic resonance hydrogen spectrum of the multi-hydrogen bond system silane coupling agent II is characterized as follows: 1 H NMR (DMSO-d6, 400MHz) δ: 0.87-0.90 (t, 2H), 1.61-1.68 (m, 2H), 1.85-1.92 (m, 4H), 2.53 (s, 6H), 3.13 (s, 3H), 3.27-3.32 (m, 4H), 3.47-3.50 (t, 2H), 3.58(s, 9H), 3.66-3.70(t, 4H), 5.90(s, 2H), 7.04-7.06(t, 2H), 7 .57-7.63(m, 8H), 7.91(s, 2H), 8.43(s, 2H), 9.57(s, 2H), 10.74(s, 2H).

[0058] Experimental Example 4:

[0059] Preparation of hydroxylated carbon fiber: 10 g of nano-carbon fiber and 200 mL of hydrogen peroxide aqueous solution (30 wt%) were added to a round-bottom flask, and dispersed evenly by ultrasonication for 10 min. Under mechanical stirring, the temperature was raised to 105 ° C and refluxed for 6 h. After cooling, it was centrifuged at 5000 rpm for 5 min, washed with deionized water 3 times, and vacuum dried at 80 ° C for 5 h to obtain hydroxylated carbon fiber.

[0060] Experimental Example 5:

[0061] (1) Preparation of interface-stable carbon fiber I carrying multiple hydrogen bond systems: The silanol functional groups obtained by hydrolysis of the multiple hydrogen bond system silane coupling agent I undergo dehydration condensation reaction with the hydroxyl functional groups on the surface of the hydroxylated carbon fiber, and the multiple hydrogen bond system silane coupling agent I is modified on the surface of the carbon fiber to prepare interface-stable carbon fiber I carrying multiple hydrogen bond systems. The specific preparation steps are as follows: 5 g of hydroxylated carbon fiber, 80 mL of anhydrous ethanol and 20 mL of deionized water are added to a beaker, ultrasonically treated for 10 min, heated to 40 ° C, and then 3 g of the multiple hydrogen bond system silane coupling agent I and 2 drops of glacial acetic acid are added to the beaker in turn, stirred for 10 h, centrifuged, and repeatedly centrifuged and washed with anhydrous ethanol and deionized water in turn, and then dried in a 50 ° C vacuum oven and a 110 ° C oven for 2 h to obtain interface-stable carbon fiber I carrying multiple hydrogen bond systems;

[0062] (2) Preparation of interface-stabilized carbon fiber II carrying a multiple hydrogen bond system: Compared with interface-stabilized carbon fiber I, the only difference is that a multiple hydrogen bond system silane coupling agent II is used to replace the multiple hydrogen bond system silane coupling agent I.

[0063] Experimental Example 6:

[0064] (1) Preparation of PE-CNF-PA-Ⅰ masterbatch. The specific process is as follows:

[0065] The formula of PE-CNF-PA-Ⅰ masterbatch is: 30wt% high-density polyethylene resin HDPE, 60wt% PA-CNF-Ⅰ composite material and 10wt% maleic anhydride grafted polyethylene resin PE-g-MAH;

[0066] The preparation method of the PA-CNF-Ⅰ composite material is as follows: the interface-stabilized carbon fiber Ⅰ carrying multiple hydrogen bonding systems on the surface of the interface-stabilized carbon fiber Ⅰ carrying multiple hydrogen bonding systems self-assembles with the amide groups on the main chain of the nylon resin PA molecule, thereby compounding the interface-stabilized carbon fiber Ⅰ with the nylon resin PA;

[0067] The mass ratio of the interface-stabilized carbon fiber Ⅰ loaded with multiple hydrogen bonding systems and the nylon resin PA in the PA-CNF-Ⅰ composite material is 2:13;

[0068] The specific experimental steps for preparing the PA-CNF-Ⅰ composite material are as follows: 13 g of nylon resin, 20 mL of anhydrous tetrahydrofuran and 80 mL of anhydrous N,N-dimethylformamide are added to a three-necked flask, the temperature is raised to 60°C and stirred until all dissolved, and under nitrogen protection, 10 mL of anhydrous tetrahydrofuran solution containing 2 g of interface-stabilized carbon fiber Ⅰ with multiple hydrogen bond systems is slowly added to the three-necked flask, the temperature is raised to 80°C and stirred for 6 h, the reaction is cooled to room temperature, the solvent is removed by rotary evaporation, and the PA-CNF-Ⅰ composite material is obtained by vacuum drying at 120°C for 8 h.

[0069] The specific experimental steps for preparing PE-CNF-PA-Ⅰ masterbatch are as follows: high-density polyethylene resin HDPE, PA-CNF-Ⅰ composite material and maleic anhydride grafted polyethylene resin PE-g-MAH are placed in a vacuum drying oven at 80°C for 12 hours, then added into a high-speed mixer according to the formula of PE-CNF-PA-Ⅰ masterbatch and mixed evenly, extruded into granules by a twin-screw extruder, and vacuum dried at 80°C for 6 hours to prepare PE-CNF-PA-Ⅰ masterbatch;

[0070] Among them, the process parameters of the twin-screw extruder are set as follows: the temperatures of zones 1-6 are 170°C, 190°C, 220°C, 230°C, 240°C, and 235°C, respectively, and the rotation speed is 300r / min;

[0071] (2) Preparation of PE-CNF-PA-Ⅱ masterbatch: Compared with PE-CNF-PA-Ⅰ masterbatch, the only difference is that PA-CNF-Ⅱ composite material is used to replace PA-CNF-Ⅰ composite material;

[0072] The preparation method of the PA-CNF-Ⅱ composite material is as follows: the interface-stabilized carbon fiber Ⅱ and the nylon resin PA are composited by self-assembling the interface-stabilized carbon fiber Ⅱ with the amide groups on the main chain of the nylon resin PA molecule through the multiple hydrogen bonding systems on the surface of the interface-stabilized carbon fiber Ⅱ with the multiple hydrogen bonding systems;

[0073] The specific experimental steps for preparing PA-CNF-Ⅱ composite materials refer to the preparation experiment of PA-CNF-Ⅰ composite materials, and the only difference is that the interface-stabilized carbon fiber Ⅱ carrying multiple hydrogen bonding systems is used to replace the interface-stabilized carbon fiber Ⅰ carrying multiple hydrogen bonding systems;

[0074] (3) Preparation of PE-CNF-PA-Ⅲ masterbatch: Compared with PE-CNF-PA-Ⅰ masterbatch, the only difference is that the formula of PE-CNF-PA-Ⅲ masterbatch is 20wt% high-density polyethylene resin HDPE, 70wt% PA-CNF-Ⅰ composite material and 10wt% maleic anhydride grafted polyethylene resin PE-g-MAH;

[0075] (4) Preparation of PE-CNF-PA-IV masterbatch: Compared with PE-CNF-PA-Ⅰ masterbatch, the only difference is that the formula of PE-CNF-PA-IV masterbatch is 40wt% high-density polyethylene resin HDPE, 50wt% PA-CNF-Ⅰ composite material and 10wt% maleic anhydride grafted polyethylene resin PE-g-MAH. Embodiment 1:

[0076] A high-stiffness toothpaste packaging tube, the product structure of which is the following layers arranged in sequence: a low-density polyethylene resin LDPE layer, an ethylene-acrylic acid copolymer resin EAA layer, an aluminum foil Al layer, an ethylene-acrylic acid copolymer resin EAA layer, and a self-made high-stiffness co-extruded layer;

[0077] The high-stiffness toothpaste packaging tube is made by compounding a 70μm thick LDPE layer, a 5μm thick EAA layer, a 10μm thick aluminum foil Al layer, a 5μm thick EAA layer and a 120μm thick self-made high-stiffness co-extruded layer through a high-speed solvent-free compounding process.

[0078] The self-made high-stiffness co-extruded layer is one of the self-made high-stiffness co-extruded layer I, the self-made high-stiffness co-extruded layer II, the self-made high-stiffness co-extruded layer III and the self-made high-stiffness co-extruded layer IV. Embodiment 2:

[0079] The self-made high-stiffness co-extruded film I used in the self-made high-stiffness co-extruded layer I in Example 1 is coextruded by the first layer, the second layer, the third layer, the fourth layer, the fifth layer, the sixth layer, the seventh layer, the eighth layer, the ninth layer, the tenth layer and the eleventh layer arranged in sequence, and the formula and dosage of each layer are as follows:

[0080] First layer: the formula is 60 parts by weight of low-density polyethylene resin LDPE, 35 parts by weight of linear low-density polyethylene resin LLDPE, 2 parts by weight of antioxidant 168, 1 part by weight of antioxidant 1010 and 2 parts by weight of anti-ultraviolet agent UV-329, with an amount of 10 parts by weight;

[0081] The second layer: the formula is 70 parts by weight of high-density polyethylene resin HDPE and 30 parts by weight of metallocene polyethylene resin m-LLDPE, the amount is 10 parts by weight;

[0082] The third layer: the formula is 60 parts by weight of low-density polyethylene resin LDPE and 40 parts by weight of metallocene polyethylene resin m-LLDPE, the amount is 5 parts by weight;

[0083] The fourth layer: the formula is 100 parts by weight of maleic anhydride grafted polyethylene resin PE-g-MAH, the amount is 2.5 parts by weight;

[0084] The fifth layer: the formula is 96 parts by weight of low-density polyethylene resin LDPE and 4 parts by weight of ethylene-vinyl alcohol copolymer resin EVOH, the amount is 10 parts by weight;

[0085] The sixth layer: the formula is 40 parts by weight of high-density polyethylene resin HDPE and 60 parts by weight of PE-CNF-PA-Ⅰ masterbatch, with an amount of 25 parts by weight;

[0086] The seventh layer: the formula is 96 parts by weight of low-density polyethylene resin LDPE and 4 parts by weight of ethylene-vinyl alcohol copolymer resin EVOH, the amount is 10 parts by weight;

[0087] The eighth layer: the formula is 100 parts by weight of maleic anhydride grafted polyethylene resin PE-g-MAH, the amount is 2.5 parts by weight;

[0088] Ninth layer: The formula is 60 parts by weight of low-density polyethylene resin LDPE and 40 parts by weight of metallocene polyethylene resin m-LLDPE, with an amount of 5 parts by weight;

[0089] The tenth layer: the formula is 70 parts by weight of high-density polyethylene resin HDPE and 30 parts by weight of metallocene polyethylene resin m-LLDPE, the amount is 10 parts by weight;

[0090] The eleventh layer: the formula is 60 parts by weight of low-density polyethylene resin LDPE and 40 parts by weight of linear low-density polyethylene resin LLDPE, with an amount of 10 parts by weight. Embodiment three:

[0091] The preparation process of the self-made high-stiffness co-extruded film I in Example 2 is as follows:

[0092] The ingredients were prepared according to the formula of the self-made high-stiffness co-extruded film I, and the raw materials of each layer were respectively put into the hoppers of eleven screw extruders of the eleven-layer co-extrusion film blow molding unit. The molten resins were merged at the die head through the splitter, and extruded and blown through the die head. The blow-up ratio was controlled at 2.6, and the self-made high-stiffness co-extruded film I with a thickness of 120 μm was prepared.

[0093] Among them, the process parameters of the screw extruder corresponding to the first, second, third, ninth, tenth and eleventh layers are set as follows: the temperature of zones 1-3 is 120°C, 150°C and 170°C respectively, the flow channel temperature is 165°C, and the speed is 30r / min;

[0094] The process parameters of the screw extruder corresponding to the fourth and eighth layers were set as follows: the temperatures of zones 1-3 were 125°C, 150°C, and 165°C, respectively, the flow channel temperature was 160°C, and the rotation speed was 15 r / min;

[0095] The process parameters of the screw extruder corresponding to the fifth and seventh layers were set as follows: the temperatures of zones 1-3 were 160°C, 180°C, and 190°C, respectively, the flow channel temperature was 185°C, and the rotation speed was 40 r / min;

[0096] The process parameters of the screw extruder corresponding to the sixth layer are set as follows: the temperatures of zones 1-3 are 200°C, 230°C, and 250°C, respectively, the flow channel temperature is 245°C, and the rotation speed is 60r / min. Embodiment 4:

[0097] The homemade high-stiffness co-extruded film II used in the homemade high-stiffness co-extruded layer II in Example 1 has a formula and dosage of each film layer that differs from the homemade high-stiffness co-extruded film I in Example 2 only in that PE-CNF-PA-II masterbatch is used to replace PE-CNF-PA-I masterbatch;

[0098] The preparation process of the self-made high-stiffness co-extruded film II is the same as the preparation process of the self-made high-stiffness co-extruded film I in Example 3. Embodiment five:

[0099] The homemade high-stiffness co-extruded film III used in the homemade high-stiffness co-extruded layer III in Example 1 has a formula and dosage of each film layer that differs from the homemade high-stiffness co-extruded film I in Example 2 only in that PE-CNF-PA-III masterbatch is used to replace PE-CNF-PA-Ⅰ masterbatch;

[0100] The preparation process of the self-made high-stiffness co-extruded film III is the same as the preparation process of the self-made high-stiffness co-extruded film I in Example 3. Embodiment six:

[0101] The homemade high-stiffness co-extruded film IV used in the homemade high-stiffness co-extruded layer IV in Example 1 has a formula and dosage of each film layer that differs from the homemade high-stiffness co-extruded film I in Example 2 only in that PE-CNF-PA-IV masterbatch is used to replace PE-CNF-PA-Ⅰ masterbatch;

[0102] The preparation process of the self-made high-stiffness co-extruded film IV is the same as the preparation process of the self-made high-stiffness co-extruded film I in Example 3.

[0103] Comparative Example:

[0104] Preparation of conventional co-extruded film: Compared with the self-made high-stiffness co-extruded film I, the only difference is that the PE-CNF-PA-I masterbatch is replaced by high-density polyethylene resin HDPE.

[0105] Performance Test:

[0106] (1) Stiffness performance test: Use PN-ST500 computer stiffness tester (resolution: 0.01mN, range: 20-10000mN, bending length: 50mm / 25mm / 10mm three gears) and PN-STC70 stiffness sampler to test the stiffness of the sample. The specific test steps are as follows: Use the stiffness sampler to cut a sample of 70×38mm in size (sample along the film blowing direction), specify the direction consistent with the length direction of the sample as the test direction, clamp one end of the sample in the sample clamp (test angle 15°, bending speed 2° / s), start the instrument, and when the chuck turns to 15°, the test stops automatically, the instrument displays the maximum bending force, and calculates the stiffness value of the sample. The specific method is as follows:

[0107] Stiffness value (mN·m) = maximum bending force × bending length;

[0108] (2) Barrier performance test: The samples were tested for oxygen permeability and water vapor permeability in accordance with GB / T 1038-2000 and GB / T 1037-2021, respectively. The specific test steps are as follows: a 30 cm round sample was placed in a glass desiccator at an ambient temperature of 25°C and anhydrous calcium chloride was used as a desiccant for 72 hours. The barrier properties of the samples were then tested using a Y110 oxygen permeability tester and a W3 / 060 water vapor permeability tester.

[0109] (3) Mechanical properties test: According to GB / T 1040.1-2018 "Determination of tensile properties of plastics", a 150 mm × 20 mm sample (sampled along the film blowing direction) was fixed on an Instron 5565 universal tensile testing machine at room temperature and a tensile test was performed at a tensile rate of 5 mm / min.

[0110] The above experimental results are shown in Table 2 and Figure 4 .

[0111] Table 2 Performance test results of self-made high-stiffness co-extruded film in high-stiffness toothpaste packaging tube

[0112]

[0113] By comprehensively analyzing the above experimental results, the following conclusions can be drawn:

[0114] Conclusion 1: The two new self-made high-stiffness co-extruded films prepared by the present invention have achieved beneficial technical effects of significantly improving stiffness performance compared with conventional co-extruded films;

[0115] Among them, the improvement effect of self-made high-stiffness co-extruded film II is the most significant;

[0116] Conclusion 2: The self-made high-stiffness co-extruded film prepared by the present invention not only has very excellent barrier properties, but also has significantly improved mechanical properties.

Claims

1. A process for preparing a high-stiffness toothpaste packaging tube, characterized in that: The high-stiffness toothpaste packaging tube is made of an outer PE film, a first adhesive layer, an intermediate aluminum foil, a second adhesive layer and an inner high-stiffness co-extruded film through a high-speed solvent-free composite process; Wherein, the preparation method of high stiffness co-extruded film is: Step 1: Preparation of PA-CNF composite material: The interface-stabilized carbon fiber and the nylon resin PA are composited by self-assembly of the multiple hydrogen bonding systems on the surface of the interface-stabilized carbon fiber carrying the multiple hydrogen bonding systems and the amide groups on the main chain of the nylon resin PA molecule; Step 2: Preparation of PE-CNF-PA masterbatch: 20-40wt% high-density polyethylene resin HDPE, 50-70wt% PA-CNF composite material and 5-15wt% maleic anhydride grafted polyethylene resin PE-g-MAH are added into a high-speed mixer and mixed evenly, and then extruded and granulated by a twin-screw extruder; Step 3: The high-stiffness co-extruded film is set to an eleven-layer co-extruded film structure, the PE-CNF-PA masterbatch is introduced into the sixth layer of the high-stiffness co-extruded film, and an eleven-layer co-extrusion blow molding film forming process is adopted to prepare a high-stiffness co-extruded film.

2. The process for preparing a high-stiffness toothpaste packaging tube according to claim 1, characterized in that: The formula and dosage of each film layer of the high stiffness co-extruded film are as follows: First layer: The formula is 50-70 parts by weight of low-density polyethylene resin LDPE, 30-40 parts by weight of linear low-density polyethylene resin LLDPE and 3-10 parts by weight of composite additives, with an amount of 5-15 parts by weight; The second layer: the formula is 60-80 parts by weight of high-density polyethylene resin HDPE and 20-40 parts by weight of metallocene polyethylene resin m-LLDPE, the amount is 5-15 parts by weight; The third layer: the formula is 50-70 parts by weight of low-density polyethylene resin LDPE and 30-50 parts by weight of metallocene polyethylene resin m-LLDPE, the amount is 3-10 parts by weight; The fourth layer: the formula is 100 parts by weight of maleic anhydride grafted polyethylene resin PE-g-MAH, the amount is 1-5 parts by weight; The fifth layer: the formula is 95-99 parts by weight of low-density polyethylene resin LDPE and 1-5 parts by weight of ethylene-vinyl alcohol copolymer resin EVOH, the amount is 5-15 parts by weight; The sixth layer: The formula is 30-50 parts by weight of high-density polyethylene resin HDPE and 50-70 parts by weight of PE-CNF-PA masterbatch, with an amount of 20-30 parts by weight; The seventh layer: the formula is 95-99 parts by weight of low-density polyethylene resin LDPE and 1-5 parts by weight of ethylene-vinyl alcohol copolymer resin EVOH, the amount is 5-15 parts by weight; The eighth layer: the formula is 100 parts by weight of maleic anhydride grafted polyethylene resin PE-g-MAH, the amount is 1-5 parts by weight; Ninth layer: The formula is 50-70 parts by weight of low-density polyethylene resin LDPE and 30-50 parts by weight of metallocene polyethylene resin m-LLDPE, with an amount of 3-10 parts by weight; The tenth layer: the formula is 60-80 parts by weight of high-density polyethylene resin HDPE and 20-40 parts by weight of metallocene polyethylene resin m-LLDPE, the amount is 5-15 parts by weight; The eleventh layer: The formula is 50-70 parts by weight of low-density polyethylene resin LDPE and 30-50 parts by weight of linear low-density polyethylene resin LLDPE, with an amount of 5-15 parts by weight.

3. The process for preparing a high-stiffness toothpaste packaging tube according to claim 1, characterized in that: The preparation method of the interface-stabilized carbon fiber carrying a multiple hydrogen bond system is as follows: a dehydration condensation reaction is carried out between the silanol functional groups obtained by hydrolyzing a multiple hydrogen bond system silane coupling agent I or a multiple hydrogen bond system silane coupling agent II and the hydroxyl functional groups on the surface of the hydroxylated carbon fiber, and the multiple hydrogen bond system silane coupling agent is modified on the surface of the carbon fiber to prepare the interface-stabilized carbon fiber carrying a multiple hydrogen bond system.

4. The process for preparing a high-stiffness toothpaste packaging tube according to claim 3, characterized in that: The chemical structural formula of the multi-hydrogen bond system silane coupling agent I is: 。 5. The process for preparing a high-stiffness toothpaste packaging tube according to claim 3, characterized in that: The chemical structural formula of the multi-hydrogen bond system silane coupling agent II is: 。 6. The process for preparing a high-stiffness toothpaste packaging tube according to claim 4, characterized in that: The preparation method of the multiple hydrogen bond system silane coupling agent I is: The -NH2 functional group of 2-amino-4-hydroxy-6-methylpyrimidine reacts with the isocyanate group of p-phenylene diisocyanate by addition reaction, and the molar ratio of 2-amino-4-hydroxy-6-methylpyrimidine to p-phenylene diisocyanate is controlled to be 1:(2-10) to generate a multi-hydrogen bond system monomer; The multiple hydrogen bond system silane coupling agent I is prepared by allowing the isocyanate group of the multiple hydrogen bond system monomer to undergo an addition reaction with the -NH2 functional group of 3-aminopropyltrimethoxysilane, and controlling the molar ratio of the multiple hydrogen bond system monomer to 3-aminopropyltrimethoxysilane to be 1:(1.01-1.08).

7. The process for preparing a high-stiffness toothpaste packaging tube according to claim 5, characterized in that: The preparation method of the multiple hydrogen bond system silane coupling agent II is: Firstly, the isocyanate group of the multiple hydrogen bond systemized monomer reacts with the -NH2 functional group of N,N-bis(3-aminopropyl)methylamine to generate a multiple hydrogen bond systemized tertiary amine monomer; Then, the tertiary amine functional group of the multiple hydrogen bond system tertiary amine monomer and the chlorine functional group of 3-chloropropyltrimethoxysilane are quaternized by the nucleophilic substitution mechanism to prepare the multiple hydrogen bond system silane coupling agent II. The molar ratio of the multiple hydrogen bond system monomer, N,N-bis(3-aminopropyl)methylamine and 3-chloropropyltrimethoxysilane is controlled to be (2.01-2.08):1:(1.01-1.08).

8. The process for preparing a high-stiffness toothpaste packaging tube according to claim 2, characterized in that: The mass ratio of the multi-hydrogen bond systemized silane coupling agent to the hydroxylated carbon fiber in the interface-stabilized carbon fiber carrying a multi-hydrogen bond system is 1:(1-5); The hydroxylated carbon fibers have a diameter of 150-200 nm and a length of 10-20 μm.

9. The process for preparing a high-stiffness toothpaste packaging tube according to claim 1, characterized in that: The mass ratio of the interface-stabilized carbon fiber carrying a multiple hydrogen bond system to the nylon resin PA in the PA-CNF composite material is 1:(5-10).

10. The process for preparing a high-stiffness toothpaste packaging tube according to claim 2, characterized in that: The composite auxiliary agent comprises 0.5-5 parts by weight of antioxidant 168, 0.1-3 parts by weight of antioxidant 1010 and 0.5-5 parts by weight of anti-ultraviolet agent UV-329.

Citation Information

Patent Citations

  • High flow carbon fiber reinforced nylon composite material with fine surface and preparation method thereof

    CN106046776A

  • Polyamide resin composition

    JP2012041526A